Needs analysis and syllabus construction of english for islamic studies in public and private universities in Malaysia - Sayed Abudhahir, Rabiathul Adhabiyyah (2021)
The lack of motivation among the Islamic Studies students in learning the English Language is seen as a stumbling block for them to be competent in the language. For students of the Islamic Studies Program, the use of English in their career path is vague or insignificant which caused them to appear apathetic towards learning the language. These graduates are also known as Da’ees who are referred to as a person who goes out into the field to talk about religious matters. To date, there is still no specific English course for students enrolled in an Islamic Studies undergraduate degree programme. Hence, this study aims to identify the needs of the Islamic Studies students which is then triangulated with the needs of the lecturers and experts from the field to design a syllabus specially for the Islamic Studies students. The Mixed Method Research design was employed to collect data to be used as a guideline to design the syllabus. The needs analysis questionnaires were completed by 782 students who were randomly selected from 13 public and private higher learning institutions in Malaysia. Furthermore, an in-depth ethnography study was conducted to identify the needs of the lecturers and experts from the field of Islamic Studies. The results indicated that the most significant quantitative findings of this study is the high preference on speaking skills which includes variety of speaking activities in the classroom. Acquiring speaking skills will help the students preach about Islam to the public effectively as well as to rectify and prevent any misinformation about Islam. Even though speaking was chosen as the most important skill, the students agreed that reading skills are also necessary to be acquired. Without acquiring the skill to read English Islamic scholarly articles, journals, and other academic reading materials, the students would not be able to convey essential teachings of Islam to their target audience. The ability to read and critically analyse English academic materials will increase their knowledge about Islamand thus make them better informers to the public. The findings from the ethnographic study revealed the need for Da’ees in using English to preach about Islam to the tourists or the local non-Muslim communities. Furthermore, the use of English is also important when conducting conversion sessions, where in most situations, they are more comfortable in using English as a medium of communication. To conclude, this study has made several contributions. Firstly, it has given a new body of knowledge to the field of English for Specific Purposes which is the introduction of English for Islamic Studies. Secondly, the development of the needs analysis questionnaire in the field of English for Islamic Studies that can be used by other researchers interested in similar goals. In addition, the development of a framework in helping and guiding ESP to design a course. Finally, a syllabus was designed based on the needs of the Islamic Studies students.